PENGARUH PROFITABILITAS, RISIKO BISNIS, UKURAN PERUSAHAAN DAN STRUKTUR ASET TERHADAP STRUKTUR MODAL PADA PERUSAHAAN REAL ESTATE DAN PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016 – 2018 - Umayroh, Harry Shinta Dyah; Irsad, Moch. (Proceeding SENDI_U, 2021)
This study aims to examine and analyze the effect of profitability, business risk, asset structure and firm size on the capital structure of Real Estate & Property companies listed on the IDX for the 2016-2018 period. This type of research is descriptive quantitative. The population in this study are all Real Estate & Property companies listed on the IDX for the 2016-2018 period. The sample selection used purposive sampling and obtained a sample of 93 companies. This study uses multiple linear regression analysis using the SPSS 19 application. The test results show that profitability has a significant negative effect on capital structure. Firm size has a positive effect on capital structure. Asset structure has no significant effect on capital structure. Business risk has no significant effect on capital structure.